PENERAPAN KRIPTOGRAFI CAESAR CIPHER PADA FITUR PESAN TEKS - Samsuriah; Ida (Nusantara Hasana Journal, 2023)
The progress of communication in the era of technological development where applications and communication support in various ways are increasingly sophisticated indicates that more and more people need access and relationships in every existing communication. Therefore, data or information security is needed to maintain confidentiality. One way to secure data or information is with Cryptology. Cryptography is the study of posting security (confidentiality), cryptographic algorithm techniques consisting of substitution and transposition techniques. Cryptographic methods or techniques can be trusted to deal with data or information security problems, because apart from using computer programming languages, cryptography also uses mathematical formulas, ranging from simple formulas to complex formulas. From the results of the study it can be concluded that with the formula used in the Caesar Cipher cryptographic method, it can be said that even though the Caesar Cipher is difficult to solve, it can be easily solved using mathematical formulas and using a programming language to obtain encryption and decryption results.